Archaeology in the Žitava Valley I : The LBK and Želiezovce Settlement Site of Vráble - Furholt, M. (2021)
The early Neolithic site of Vráble (5250-4950 cal BCE) is among the largest LBK settlement agglomerations in Central Europe, and exceptional within the southwest Slovakian area. Geophysical surveys revealed more than 300 houses, grouped into three contemporary neighbourhoods, one of which is delineated by a complex ditched enclosure system. This enclosure is associated with a large number of human remains, which reveal new patterns of burial and deposition practices. This volume presents the first part of the results of an international research project that was started in 2012 and aims to explore the social implications of settlement concentration in the context of early farming communities, on the background of subsistence patterns and landscape use.This is the first volume of "Archaeology in the Žitava valley", and it presents the finds, features and data uncovered and synthesised from our archaeological, pedological, geophysical, archaeobotanical, anthropological, zoo-archaeological and stable isotope studies on the site of Vráble "Veľké Lehemby" and "Fárske" in southwest Slovakia. These data are used to reconstruct the social and economic patterns and social processes, highlighting a growing tension between incentives of cooperation and sharing vs. monopolisation of resources and individual interests, driving the 300-year history of this site until its total abandonment. While the history of Vráble is unique, it holds clues for a better understanding of the overall, central European phenomenon of large, enclosed settlements of the later LBK, their association with rituals and violence involving human bodies, and the end of the LBK social world.